PENGARUH KEADILAN ORGANISASIONAL TERHADAP KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL POLÍCIA NACIONAL DE TIMOR-LESTE (PNTL) - Saldanha, Lino Da Silva; Supartha, Wayan Gede; Riana, Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.02.TAHUN 2019, 2019)
The term of organizational justice used in this study was the degree to which organization member perceived about the overall organizational procedures, rules, and policies which are connected to their job.  The aim of this study was to explore the quality, strength, and significance of the relationship between three types of organizational justices (procedural, distributive and interactional) to job satisfaction and organizational commitment. The study would investigate the relationship between organization chief agent  in the Polícia Nacional De Timor-Leste (PNTL).  Data was collected through questionnaire and the data which had been collected and be analyzed using descriptive and path analysis. The results showed that the perception of chief agent member in the PNTL about organizational justice had a positive significan effect on their job satisfaction. This research also found that the job satisfaction of chief agent member had a positive significan effect on organizational commitment in the Polícia Nacional De Timor-Leste (PNTL).